The intellect of Abū Hāmid Al-Ghazālī in dealing with the Qur’anic scientific exegesis - Ahmad Yunus Mohd Noor,; Zetty Nurzuliana Rashed,; Asmilyia Mohd Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Abū Hāmid al-Ghazālī is considered one of the prominent Muslim thinkers and scholars in the traditional Muslim world. He has produced numerous intellectual sources comprehensively. This paper aims to analyze Abū Hāmid al-Ghazālī’s views on dealing with the scientific exegesis. This was investigated from his thoughtful and broad understanding of its principle and underlying purpose. The essential understanding of the principle of scientific exegesis was analytically discussed in his magnum opus; Jewels of the Qur’ān. To reach a representative conclusion, this study undertakes an analysis of the al-Ghazālī view, promotes intellectual discourse, and venerated exegesis as the main sources of reference by adopting the document analysis method. The finding shows that Abū Hāmid al-Ghazālī’s discussion on scientific exegesis emphasized on relevance to contemporary practice and the modern context of Islam. It set forth an important framework and methodology for the integration of the Quran and science. This leads to the collaboration between two branches of knowledge and has come to be known as ‘scientific exegesis’ that the Qur’ān contains verses that point to scientific discoveries such as the roundness of the earth; the orbit of the earth around the sun; and the uniqueness of human fingerprints. It will provide students, educators, researchers, and scholars with a resource for understanding and responding to faithful Islamic sciences issues that are of concern to contemporary Islam and to society.